IDENTIFIKASI POTENSI HUTAN MANGROVE SEBAGAI PENGUAT KAWASAN EKOWISATA DI PESISIR BALE-BALE - Wenang Anugoro; Muhammad Zainuddin; Andi Andi (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2019)
Technological advances in UAV (Unmanned Arial Vehicle) photogrammetry have been more efficient and accurate in the field of mapping and monitoring surveys. This study aims to determine the level of potential mangrove forests seen from the density of its vegetation, mangrove species and know how the relationship to marine biota contained in coastal areas bale-bale Batam. The recording data was taken on 26-08-2017. The method used to determine the density is the transformation of the NDVI vegetation index combined with the field transect. the field transect was conducted to see the species and biota of its association contained in each type of mangrove forest vegetation. The results of this study indicate that mangrove in coastal bale-bale has an area of 4.915 Ha, with the potential of mangrove forest area is still in potential condition seen from the extraction vegetation density from the transformation of vegetation index used and with the identification of mangrove species that is Avecennia and Rhizopora, relationship with the type of biota association Ocypodidae, Coenobitadae, and Gobiidae especially for Rhizopora mangrove species, it is because rhizopora is the most dominant type of mangrove in the research location.